Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Pekerja Bagian Produksi PT. X Tahun 2025 - Adilla Desta; Usi Lanita; Andree Aulia Rahmat; Willia Novita Eka Rini; Ashar Nuzulul Putra (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Work fatigue is one of the factors that contribute to decreased productivity and increased risk of occupational accidents. This study aims to analyze various factors associated with work fatigue among production workers at PT. X in 2025. The research employed an analytical quantitative design with a cross-sectional approach. The sample consisted of 53 respondents selected using total sampling. Data were collected through questionnaires covering worker characteristics (age, nutritional status, medical history, smoking habits, years of service, and work stress) as well as levels of work fatigue. Data analysis was conducted using the chi-square test. The findings revealed that 56.6% of workers experienced high levels of fatigue. There were significant associations between age (p=0.023; PR=1.836), nutritional status (p=0.021; PR=1.786), medical history (p=0.025; PR=1.789), smoking habits (p=0.039; PR=1.706), years of service (p=0.015; PR=1.912), and work stress (p=0.032; PR=0.574) with work fatigue. The results indicate that workers who are at-risk age (≥35 years), have abnormal nutritional status, a history of illness, smoking habits, and longer years of service are more likely to experience work fatigue. However, high work stress showed a negative relationship, suggesting a protective effect against fatigue. In conclusion, there is a relationship between age, nutritional status, medical history, smoking habits, years of service, and work stress with work fatigue among production workers at PT. X.